Media Coverage of FDA Drug Safety Communications about Zolpidem: A Quantitative and Qualitative Analysis. Issue 5 (4th May 2017) - Woloshin, Steve; Schwartz, Lisa M.; Dejene, Sara; Rausch, Paula; Dal Pan, Gerald J.; Zhou, Esther H.; Kesselheim, Aaron S.
Abstract : FDA issues Drug Safety Communications (DSCs) to alert health care professionals and the public about emerging safety information affecting prescription and over-the-counter drugs. News media may amplify DSCs, but it is unclear how DSC messaging is transmitted through the media. We conducted a content analysis of the lay media coverage reaching the broadest audience to characterize the amount and content of media coverage of two zolpidem DSCs from 2013. After the first DSC, zolpidem news stories increased from 19 stories/week in the preceding 3 months to 153 following its release. Most (81%) appeared in the lay media, and 64% focused on the DSC content. After the second DSC, news stories increased from 24 stories/week in the preceding 3 months to 39 following. Among the 100 unique lay media news stories, at least half correctly reported three key DSC messages: next-day impairment and drowsiness as common safety hazards, lower doses for some but not all zolpidem products, and women's higher risk for impairment. Other DSC messages were reported in fewer than one-third of stories, such as the warning that impairment can happen even when people feel fully awake. The first—but not the second—zolpidem DSC generated high-profile news coverage. The finding that some messages were widely reported but others were not emphasizes the importance of ensuring translation of key DSC content.